Reflectance Confocal Microscopy and Electrical Impedance Spectroscopy in the Early Detection of Melanoma in Changing Lesions during Long-term Follow-up of Very High-risk Patients - Marion Chavez-Bourgeois; Simone Ribero; Alicia Barreiro; Natalia Espinoza; Cristina Carrera; Adriana Garcia; Llucia Alos; Susana Puig; Josep Malvehy (Medical Journals Sweden, 2022)
Electrical impedance spectroscopy has clinical relevance in diagnosing malignancy in melanocytic lesions. Sixty-eight lesions with changes during digital follow-up of patients at very high risk of developing melanoma were prospectively included in this study from February to December 2016. Electrical impedance spectroscopy and reflectance confocal microscopy were performed to evaluate their performance in this subset of difficult lesions. Forty-six lesions were considered suspicious on reflectance confocal microscopy and were excised, of these, 19 were diagnosed as melanoma. Fifteen melanomas were detected by electrical impedance spectroscopy, while 4 received a score lower than 4, which suggested no malignancy. The addition of reflectance confocal microscopy improves accuracy while maintaining the same sensitivity. In the case of electrical impedance spectroscopy scores <4, lesions exhibiting changes in follow-up may need short-term monitoring or excision if dermoscopy shows criteria for melanoma. Results of electrical impedance spectroscopy in this subset of very early lesions should be carefully considered due to the risk of false negatives.